GAMBARAN HISTOLOGI ORGAN EKSTRAMURAL Iguana iguana SEBAGAI REPTIL HERBIVORA - , YOSUA KRISTIAN ADI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Iguana iguana is a herbivorous reptile that first domesticated. During last few years, iguana lovers community increase. The problem that often occurs in maintenance of reptiles is digestion. Research on the histological structure of the extramural organ as a support of the digestive system not yet done. The aims of this study is to determine the histological structure of extramural organ of Iguana iguana as herbivorous reptiles. Three (five month old) Iguana iguana were anastized with chloroform. Laparatomy was done to collect the extramural organs (liver, vesica fellea, pancreas, and mandible). Organs were prepared and fixed with Bouin's solution for 24 hours, transferred to 70% alcohol, and then processed by paraffin method. Prior to processing, the mandible decalcified using 10% EDTA solution. Tissue were cut with a thickness of 5Î¼m and continued stained with Hematoxylin Eosin (liver, vesica fellea, pancreas, mandibular), Alcian Blue-Periodic Acid Schiff (mandible), and Gomori (mandible). Histological structure of Iguana iguanaâs extramural organs is not different from other reptiles and mammals in general. Infralabial gland is consist of serous and mucous cells. Alcian Blue-Periodic Acid Schiff and Gomori staining can indicate the presence of acid mucopolysaccharides and lipoproteinlipase in infralabial gland. Liver parenchymal hepatocytes are arranged in the form of plates radier in the area near the central vein, the lobulation is unclear, hepatic triad and Melano-Macrophage centers scattered around the central vein. Vesica fellea is lined by simple columnar epithelium intermitted by pseudostratified columnar epithelium. Pars exocrine pancreatic gland acinus composed of coneshaped cells/pyramidal similar to serous cells in salivary gland and duct system is lined by squamous epithelium, cuboidal epithelium and continue columnar simple epithelium prior to the duodenum.